Effect of Solvent Polarity on Extraction Yield, Phytochemical Composition, and Antioxidant Activity of Curcuma xanthorrhiza Roxb. and Moringa oleifera Lam. - Vina Octavia Azzahra; St Mardiana; Suharyadi Suharyadi; Rini Juita Sianipar; Dwi Sapri Ramadhan (Biology, Medicine, & Natural Product Chemistry, 2025)
The present study investigated the effect of solvent polarity on extraction yield, phytochemical composition, and antioxidant activity of Curcuma xanthorrhiza Roxb. rhizomes and Moringa oleifera Lam. leaves. Maceration was carried out using ethanol, acetone, ethyl acetate, and n-hexane for 72 hours (1:10 w/v). Extraction yield, total phenolic content (TPC), total flavonoid content (TFC), and DPPH radical scavenging activity were determined. Results demonstrated a clear polarity-dependent trend. Ethanol yielded the highest extract recovery for both species (17.55 ± 0.97% and 22.93 ± 0.65%), while n-hexane showed the lowest yield. Ethanol extracts exhibited the greatest TPC and TFC values, 47.12 mg GAE/g and 6.76 mg QE/g for C. xanthorrhiza, and 25.91 mg GAE/g and 4.67 mg QE/g for M. oleifera, respectively. Correspondingly, ethanol fractions displayed the strongest antioxidant activity with IC50 values of 22.70 and 29.80 mg/mL, indicating an inverse correlation between phenolic load and radical scavenging capacity. The study confirms that solvent polarity is a critical determinant of phytochemical recovery and antioxidant potency. The novelty of this work lies in the first comparative evaluation of C. xanthorrhiza and M. oleifera extracted under identical solvent systems, providing a rational framework for solvent selection in phytopharmaceutical and nutraceutical applications. Further work should isolate and characterize the active antioxidant constituents from the most potent extracts.